Future Skills of Science Graduate Teachers in Teaching Industry: Curriculum Implications on STEM Education - Camara, Jun S.; Adom, Dickson (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
Assessing how could an educator catch up with the evolving world necessitates the need to assess the skills he or she possess for such a future. This study sought to assess the level of competence of graduate science teachers in the Pangasinan State University across 17 future skills. Also, it aimed at correlating the level of competence of science graduate teachers across gender, age, and academic levels. The study was carried out using a cross-sectional descriptive survey under the quantitative research design. The quantitative data garnered were analyzed using descriptive statistics via SPSS version 25.0. The results of the study show very high competence in four future skills (communication competence, reflective competence, Initiative and Performance Competence, and cooperation competence) and high competence in the remaining thirteen future skills. Also, based on the computed p-values there was no significant relationship observed in all of the 17 future skills in relation to gender and academic levels of respondents. All future skills remained the same across age levels except Doctoral-level graduate teachers who had higher levels of self-competence than master-level graduate teachers. The results of the study suggest that future skills may be consciously integrated across the postgraduate curriculum of Higher Education Institutions to help develop industry-driven graduates who are prepared for the world of work.